Student's perception towards Twitter application as an educational tool innovation: Jawitweet / Nurulashiquin Ahmad Japri, Hani Syafiqah Kamarudin and Syamilin Abdul Kadir - Ahmad Japri, Nurulashiquin; Kamarudin, Hani Syafiqah; Abdul Kadir, Syamilin (2017)
Jawi script is the Malay community identity and had played a very important role in civilization and knowledge significantly in the spread of Islamic knowledge in the ASEAN region (Ibrahim, 2015). As indicated by R.J Wilkinson dictionary, the word 'Jawi' in the Malay dialect is utilized to depict a tree called 'jejawi' and it likewise knows a sort of rice. More importantly, Jawi is the Malay language written with the use of Arabic alphabet or script. It came into use as a successor to Sanskrit. The first evidence for the use of the Jawi script in the Malay Peninsula is sometimes traced to the Terenganu stone (Batu Bersurat Terengganu). While from another researcher, they said that Jawi script is one of the writings of Malay heritage (Baba, 2014). Jawi script should be protected and preserved so that it does not perish due to modernity. This is because Jawi script is a heritage that should be preserved. While according to Sulaiman (2013) and Yusoff (2005), Jawi script is one of the medium for transmitting knowledge among Muslims in Malaysia. In addition, Jawi script is also used to solve daily activities in trade, law, politics and affairs in Malaysia.